The Relationship between Self-Concept and Academic Procrastination in Al-Washliyah 3 High School Students in Medan - Tendang, Yopa Jelita; br Ginting, Eki Widiyananda; Hasanah, Wardatul Hasanah; Pohan, Meliya Rahmah; Sembiring, Sukma; Ramadhani, Ramadhani (Jurnal Ilmiah Mandala Education (JIME), 2025)
Students' self-concept is very important because it can influence learning motivation, engagement, and academic achievement. Meanwhile, academic procrastination is the behavior of postponing academic tasks or obligations that should be completed. The aim of this research is to determine the extent of self-concept and academic procrastination in students and to find out whether there is a relationship between self-concept and academic procrastination at SMA Al-Washliyah 3 Medan. The population of this study was SMA Al-Washliyah 3 Medan and the research sample was all 24 students in class X-C. The data collection method used is the self-concept scale and academic procrastination. This research uses a quantitative approach with correlational methods. Based on the results of data analysis regarding the relationship between self-concept and academic procrastination in students which was carried out using a correlation test in this study, the correlation coefficient value was (r) 0.519 and the significant value (p) was 0.009 (p<0.05). The results of this research state that there is a relationship between self-concept and academic procrastination in students at SMA Al-Washliyah 3 Medan. The correlation coefficient value also explains that the better a student's self-concept, the less academic procrastination behavior they carry out.